Development of Women's Fiqh Learning in State Islamic Senior High Schools: Integration of Islamic Gender Education Theory, Inquiry-Based Learning, and Strengthening of Islamic Character - Teguh Luhuringbudi; Fitri Liza; Panggih Abdiguno; Edi Kurniawan; Dewi Nita Utami; Abdulnasir Dhaw Alsayd (NALAR FIQH: Jurnal Hukum Islam, 2025)
This research examines a crucial problem in women's fiqh education at Madrasah Aliyah: the dominance of normative-textual approaches that provide minimal space for critical dialogue on contemporary social dynamics and female identity. The study aims to design an integrated learning model for women's fiqh through a combination of Islamic Gender Education Theory, Inquiry-Based Learning, and Islamic Character Strengthening Philosophy. Data collection methods included online surveys via Google Forms, analysis of Grade XI fiqh textbooks, and examination of the classical text Ris?lah al-Ma???. Data analysis employed three theoretical frameworks: Sharia contextualism according to Zainah Anwar, inquiry cycle theory by Margus Pedaste, and personality transformation philosophy by Syed Muhammad Naquib al-Attas.Research findings reveal that although the majority of students perceive menstrual regulations as fair, their understanding remains static without critical reflection on cultural and gender contexts. The integration of these three approaches proved effective in creating a more participatory, inclusive, and meaningful learning experience. The study concludes that a paradigm shift is necessary—from information transfer to transformative educational processes. Research limitations include a narrow geographical scope and a predominantly female respondent base. The novelty of this research lies in its multi-dimensional integration approach, which has not been widely explored in academic literature. Recommendations for future research include direct implementation testing across diverse regions and the development of specific Islamic character assessment instruments tailored to women's fiqh education contexts. This model is expected to serve as an alternative learning approach that is more responsive to the needs and social realities of contemporary Muslim women, bridging traditional Islamic scholarship with modern pedagogical methodologies while maintaining religious authenticity and promoting gender-sensitive understanding